(Re)Defining Torture: Jurisprudential Cross-fertilisation in the Context of Torture - Lundgren,Engla (2025)
This thesis examines the phenomenon of legal cross-fertilisation by analysing how the ad hoc International Criminal Tribunal for the former Yugoslavia have implemented International Human Rights Law with regard to the defini-tion of torture. This thesis employs the legal dogmatic method with an emphasis on the sources of law in International Law. Two cases from the ICTY have been the subject of analysis to this paper, Delalić and Kunarac. The essay accounts for in what manner the Trial Chamber examine what requirements constitute the prohibition of torture, as prescribed in the Geneva Conventions of 1949. In the case of Delalić, the TC argued that the involvement of a public official was one of the constitutive elements of torture, but subsequently overturned this position in the Kunarac case. Instruments from International Human Rights Law was used as a basis for examination in both cases, and initially, the definition of torture was verbatim adopted from a Human Rights Instru-ment. In Kunarac, the Trial Chamber conversely assume a more critical view of cross-fertilisation. The TC highlights the structural differences between Inter-national Criminal Law and International Human Rights Law, while consulting a broader selection of sources to find support for this argument. The study finds that in Delalić, the TC employed a flawed method for inter-preting the Human Rights instruments, and, in Kunarac, it is suggested they may have ultimately arrived at a broader definition of torture than warranted. The essay argues that the broadened definition endangers the specialised na-ture of the offence and risks its trivialisation. The essay underlines the potential of harmonisation between fragmented sys-tems of International Law through the use of trans-judicial dialogue, as well as cautions for when it is applied without careful consideration.
Keywords: Folkrätt; Cross-fertilisation; Torture